2013
DOI: 10.1021/ja411146x
|View full text |Cite
|
Sign up to set email alerts
|

Polycationic Ligands in Gold Catalysis: Synthesis and Applications of Extremely π-Acidic Catalysts

Abstract: Very often ligands are anionic or neutral species. Cationic ones are rare, and, when used, the positively charged groups are normally appended to the periphery of the ligand. Here, we describe a dicationic phosphine with no spacer between the phosphorus atom and the two positively charged groups. This structural feature makes its donor ability poorer than that of phosphites and only comparable to extremely toxic or pyrophoric compounds such as PF3 or P(CF3)3. By exploiting these properties, a new Au catalyst h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 53 publications
2
102
0
6
Order By: Relevance
“…The IR spectra of the rhodium(I), tungsten(0), and molybdenum(0) carbonyl complexes 2 , 4 , and 5 demonstrate clearly that the carbene–phosphinidene adducts 1a – 1c act as strong electron‐donating phosphorus ligands; substantially lower CO stretching frequencies are observed in comparison with those of complexes with other important ancillary ligands such as phosphines and N‐heterocyclic carbenes. In view of the potential application of carbene–phosphinidene ligands in homogeneous catalysis, it can be concluded that these systems are particularly electron‐rich additions to the large family of P‐based ligands, whereas related cationic NHC‐based phosphorus ligands such as phosphenium cations of the type [(NHC)PR 2 ] + were presented recently as electron‐poor and strongly π‐accepting ligands . The NHC skeleton and also the phosphinidene moiety in NHC · PR ligands can be varied extensively to fine‐tune the electronic and steric properties to adapt to the demands of a specific catalytic process.…”
Section: Discussionmentioning
confidence: 99%
“…The IR spectra of the rhodium(I), tungsten(0), and molybdenum(0) carbonyl complexes 2 , 4 , and 5 demonstrate clearly that the carbene–phosphinidene adducts 1a – 1c act as strong electron‐donating phosphorus ligands; substantially lower CO stretching frequencies are observed in comparison with those of complexes with other important ancillary ligands such as phosphines and N‐heterocyclic carbenes. In view of the potential application of carbene–phosphinidene ligands in homogeneous catalysis, it can be concluded that these systems are particularly electron‐rich additions to the large family of P‐based ligands, whereas related cationic NHC‐based phosphorus ligands such as phosphenium cations of the type [(NHC)PR 2 ] + were presented recently as electron‐poor and strongly π‐accepting ligands . The NHC skeleton and also the phosphinidene moiety in NHC · PR ligands can be varied extensively to fine‐tune the electronic and steric properties to adapt to the demands of a specific catalytic process.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Alcarazo and co‐workers reported that platinum(II) and gold(I) complexes selectively catalyzed the 6‐ endo cycloisomerization of diverse challenging ethynylbiaryl substrates under mild reaction conditions. In particular, the cationic gold catalyst enabled the cycloisomerization of 2′,6‐disubstituted 2‐ethynylbiphenyls, affording highly strained 4,5‐disubstituted phenanthrenes even at room temperature 12b. In these examples, strong π‐acid ligands, 2,3‐dialkylaminocyclopropenium‐substituted phosphines, play important roles in the electrophilic activation of the ethynyl moiety, thus facilitating the desired 6‐ endo cycloisomerization.…”
Section: Introductionmentioning
confidence: 99%
“…B. mit Au und Cr), die auf DFT-Niveau hinsichtlich ihrer elektronischen Struktur und der Bindungsverhältnisse charakterisiert wurden. [71] Die ausgeprägten p-Akzeptoreigenschaften von Phosphor-Trikationen [69] kçnnen in der Platin(II)-Katalyse [72] und in der Goldkatalyse [73] genutzt werden, um sehr anspruchsvolle Cyclisierungsreaktionen durchzuführen. Gemeinsame Projekte mit der Alcarazo-Gruppe Die Forschung in der Alcarazo-Gruppe zielt auf das Design und die Synthese ungewçhnlicher Liganden und Koordinationsverbindungen und deren Anwendung in neuartigen katalytischen Umsetzungen.…”
Section: Gemeinsame Projekte Mit Der Fürstner-gruppeunclassified
“…Gemeinsame Projekte mit der Alcarazo-Gruppe Die Forschung in der Alcarazo-Gruppe zielt auf das Design und die Synthese ungewçhnlicher Liganden und Koordinationsverbindungen und deren Anwendung in neuartigen katalytischen Umsetzungen. [73] 3.4. Beispiele für solche Studien sind die Analyse der elektronischen Struktur in dem erstmals beobachteten Dihydridoborenium-Kation, [68] in Carben-stabilisierten Phosphor(III)-zentrierten Trikationen, [69] in Car-.…”
Section: Gemeinsame Projekte Mit Der Fürstner-gruppeunclassified